Low nanomolar affinity to major grass pollen allergen Phl p 5 as achieved in an unmutated human antibody-lineage ancestor - Essén, Mattias; Franciskovic, Eric; Sele, Céleste; Godzwon, Magdalena; Ohlin, Mats (Frontiers in Immunology, 2025)
BackgroundGroup 5 allergens, such as Phl p 5 of timothy grass, are major contributors to grass pollen allergy. Antibody 212597 specific for this allergen was recently isolated by single cell sequencing of bone marrow B cells of a grass pollen-allergic subject. This antibody, although subjected only to a low level of hypermutation resulting in six amino acid substitution across the heavy and light chain variable domains, has achieved sub-nM affinity for the allergen, suggesting that antibodies specific for this major group of allergens can be of high affinity even at the naïve, unmutated stage. The present study was designed to assess affinity and biophysical characters of the antibody, its inferred unmutated ancestor, and other intermediate and allelic variants thereof.MethodsSite-directed mutagenesis was used to revert substitutions of antibody 212579. Mutants, including its inferred unmutated common ancestor were characterized with respect to allergen affinity, thermostability, and hydrodynamic radius.ResultsWe demonstrate that even the antibody’s inferred unmutated common ancestor shows high affinity for the allergen in the low-nM range. Glutamate at heavy chain position 38, a residue unique to allele IGHV3-48*03, the germline gene origin of the heavy chain of antibody 212579, was critical for high affinity binding. Substitution to serine as found in other alleles of IGHV3–48 reduced the affinity about 20-fold. A substitution, N40HT in the heavy/light chain variable domain interface, introduced into the antibody through somatic hypermutation, did not impact its affinity for the allergen but reduced its thermal stability and increased its hydrodynamic radius.ConclusionUnmutated, high affinity (low-nM) antibodies specific for a major allergen (Phl p 5) can be generated directly in naïve B cells and are, given an appropriate rearrangement, imprinted into the repertoire through rearrangements involving immunoglobulin germline gene alleles IGHV3-48*03 and IGKV3-20*01. This specificity depends on an allele-unique residue encoded by the immunoglobulin germline repertoire. Substitutions in the heavy/light chain variable domain interface, such as N40HT in a heavy chain variable domain, might negatively impact biophysical properties of the antibody and should be considered as targets for further evolution or reversion if they negatively impact an antibody’s developability properties.